Selected Fresh and Hardened Self Compacting Concrete Incorporating PP Macro Fibers, Crushed Brick Aggregate, and Fly Ash - Sofyan, Muhammad; Lestari, Endah; Amiruddin, Aswar; Kustanrika, Irma Wirantina (Engineering, Technology & Applied Science Research, 2025)
The increasing demand for high-performance concrete that can flow and compact itself without the aid of mechanical compaction has driven the development of more efficient and sustainable Self-Compacting Concrete (SCC). The novelty of this study lies in the comprehensive evaluation of SCC incorporating a unique combination of Crushed Brick Aggregate (CBA), Polypropylene (PP) macro fibers, and varying Fly Ash (FA) content, which has not been extensively explored in previous studies. Unlike conventional SCC studies, this work systematically investigated the influence of different FA replacement levels on both the fresh and mechanical properties of an SCC mix containing CBA, a material known for its high water absorption and lower strength compared to natural aggregates. The findings provide critical insights into optimizing FA content to enhance SCC workability while mitigating the potential strength reduction associated with excessive cement substitution and CBA’s physical characteristics. The results show that the addition of FA increased the slump flow, decreased the V-funnel flow time, and increased the L-box blocking ratio, with the best results having been achieved with 30% and 40% FA content. In addition, at 20% FA content, there was a significant increase in compressive strength, flexural strength, and elastic modulus compared to the control sample without FA. This study demonstrates that FA at a content of 20% yielded the best results in improving SCC performance both in fresh and hardened conditions, whereas a higher FA content decreases the mechanical properties of concrete.